2017
DOI: 10.1111/aor.12979
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, Risk Factors, and Outcomes of Hyperbilirubinemia in Adult Cardiac Patients Supported by Veno‐Arterial ECMO

Abstract: The aims of this study were to evaluate the incidence, risk factors, and outcomes of hyperbilirubinemia in cardiac patients with veno-arterial (VA) ECMO. Data on 89 adult patients with cardiac diseases who received VA ECMO implantation in our hospital were retrospectively reviewed. All patients were divided into the following three groups: 24 in normal group (N, total bilirubin [TBIL] ≤3 mg/dL), 30 in high bilirubin group (HB, 6 mg/dL ≥ TBIL > 3 mg/dL), and 35 in severe high bilirubin group (SHB, TBIL > 6 mg/d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 26 publications
(34 reference statements)
0
15
0
Order By: Relevance
“…Perioperative hyperbilirubinemia of cardiac surgery is characterized by increased UCB, especially in the first 48 h after surgery [22,23]. The main source of UCB is hemolysis by CPB or other mechanical circulatory assist devices [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…Perioperative hyperbilirubinemia of cardiac surgery is characterized by increased UCB, especially in the first 48 h after surgery [22,23]. The main source of UCB is hemolysis by CPB or other mechanical circulatory assist devices [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…In this respect, some studies have identified serum bilirubin levels as a potential indicator of liver dysfunction following cardiac insults. For example, Lyu et al have demonstrated that very high levels of serum bilirubin (> 3 mg/dL) following veno-arterial extracorporeal membrane oxygenation (ECMO) was associated with low in-hospital survival rate [34]. Very high serum bilirubin has been associated with poorer prognosis in patients with heart failure (HF) and serum bilirubin concentration could be an independent predictor of mortality and may improve risk stratification [35].…”
Section: Bilirubin and Cardiorenal Protectionmentioning
confidence: 99%
“…However, in cases of risk factors, such as the insufficient flow in the outflow cannula leading to a rise in the negative pump head pressure, necessity of a high blood flow, or development of pump head thrombosis, severe hemolysis can occur and is reported in up to 5% of patients [ 54 ]. Lyu et al retrospectively observed, in a total of 84 VA-ECMO patients, that increased levels of plasma free Hb are associated with acute renal failure [ 55 ]. Omar et al even identified severe hemolysis (peak plasma free Hb > 500 mg/L) as an independent predictor of worse outcome [ 56 ], although data in this field remain controversial and further studies are needed.…”
Section: Complications Of Va-ecmo Therapymentioning
confidence: 99%